Spatio-temporal trend analysis and future projections of precipitation at regional scale: a case study of Haryana, India. Issue 5 (11th April 2022) - Chauhan, Abhilash Singh; Singh, Surender; Maurya, Rajesh Kumar Singh; Rani, Alka; Danodia, Abhishek
Abstract: In this study, we investigated the spatio-temporal distribution and performance of seasonal precipitation in all districts of Haryana, India. We analysed the gridded precipitation dataset of the India Meteorological Department (IMD) for a period of 120 years (1901–2020) using different statistical methods. We found that Haryana received a mean precipitation of 37.0, 37.7, 468.3, and 24.8 mm during the winter, pre-monsoon, monsoon, and post-monsoon seasons, respectively. During each season, the eastern districts of Haryana received more precipitation than its western counterparts. Sen's slope results obtained after trend-free pre-whitening (TFPW) showed a statistically significant increasing trend of 0.12 mm ( p -value; 0.04) during the pre-monsoon period, whereas decreasing but non-significant trends were observed during the winter, monsoon and post-monsoon seasons at the rate of −0.04 mm ( p -value; 0.49), −0.26 mm ( p -value; 0.52), −0.05 mm ( p -value; 0.33) per year, respectively, for the entire Haryana state. The winter precipitation is expected to increase under the Representative Concentration Pathway 4.5 (RCP4.5) scenario, whereas pre-monsoon precipitation is expected to decrease under the RCP8.5 scenario by the end of the 21st century. The monsoon precipitation is expected to decrease under all RCP scenarios, whereas post-monsoon precipitation is expected to gradually increase under the RCP8.5 scenario by the end of the 21st century. HIGHLIGHTS: Spatio-temporal distribution, variability, trends, categorization analysis of precipitation for different seasons. Most stable and variable precipitation was observed during monsoon and post-monsoon season respectively. Declining trend in precipitation observed during winter, post-monsoon and summer monsoon season while increasing trend was observed during pre-monsoon season. Future precipitation projections shows increasing/decreasing trend in different seasons under RCP2.6, RCP4.5 and RCP8.5 scenario by the end of 21st century. Graphical Abstract